The Evaluation of Fiscal Decentralization in Indonesia Based on the Degree of Regional Autonomy - Siregar, Baldric; Badrudin, Rudy (Journal of Reviews on Global Economics, 2019)
The implementation of regional autonomy in Indonesia has lasted almost 18 years. However, the success of regional autonomy has not been optimal. Some researchers discovered the existence of limitation of Regional Government Budget. This study investigates the presence of the degree of regional autonomy and its impact on social welfare using data covering all districts in Indonesia from 2013 to 2016. To test hypotheses, we first group districts based on the degree of regional autonomy and than test the existence of the degree of regional autonmy and its impact on social welfare simultaneously on each of regional autonomy degree. Partial Least Square release 6 is used to test hypotheses. The results show that the fiscal decentralization has a significant effect on capital expenditure in districts' APBD in Indonesia but has no significant effect on economic growth and social welfare of districts in Indonesia; capital expenditure in districts' APBD in Indonesia has a significant effect on the economic growth and social welfare of the districts in Indonesia; and economic growth has no significant effect on the social welfare of the districts in Indonesia. The significance of the influence between variables depends on the degree of regional autonomy.